2018
DOI: 10.1515/intag-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition changes and aeration time on the structure and rehydration of innovative freeze-dried gels

Abstract: This paper seeks to explain the structural effect on selected properties of freeze-dried gels with different compositions and aeration times. Herein, sugars and citric acid were added to gels with low-methoxyl pectin, mixtures of xanthan gum and locust bean gum, as well as xanthan gum and guar gum, in order to obtain a strawberry model. Strawberry pulp was also added to hydrocolloids to develop an innovative strawberry product. All samples were aerated for 3 and 7 min, and freeze-dried. Composition changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…They showed that hydrocolloids can improve the texture of dairy products by increasing their viscosity, but also that they may interact with different components of products, which changes the properties of dairy products. Similar effects may be obtained in freeze-dried vegetables or fruit bars as an effect of sample composition, different ingredients and pH, acid and sugar content [83].…”
Section: Properties Of Dried Gels and The Effect Of Different Ingredisupporting
confidence: 58%
See 4 more Smart Citations
“…They showed that hydrocolloids can improve the texture of dairy products by increasing their viscosity, but also that they may interact with different components of products, which changes the properties of dairy products. Similar effects may be obtained in freeze-dried vegetables or fruit bars as an effect of sample composition, different ingredients and pH, acid and sugar content [83].…”
Section: Properties Of Dried Gels and The Effect Of Different Ingredisupporting
confidence: 58%
“…In the literature there are few publications about dried fruit or vegetable gels. Strawberry pulp added to the low-methoxyl pectin, the mixture of xanthan gum and locust bean gum or mixture of xanthan gum and guar gum allowed obtaining a porous structure attractive for consumers, what was confirmed by e.g., sensory analysis ( Figure 6) [60,83]. The porous structure of gel matrix was also created by different aeration time (3, 5, 7 and 9 min).…”
Section: Properties Of Dried Gels and The Effect Of Different Ingredimentioning
confidence: 64%
See 3 more Smart Citations